2009
DOI: 10.1590/s0102-09352009000100031
|View full text |Cite
|
Sign up to set email alerts
|

Breeder age and bone development in broiler chicken embryos

Abstract: The effect of breeder age on long bone development was studied in chicken embryos from 12 days of incubation until hatching. Fertile eggs were incubated and randomly assigned in a 2 x 6 factorial arrangement (two breeder ages -38 and 60 weeks and six incubation days -12, 14, 16, 18, 20, and 21). Enzymatic activity of acid and alkaline phosphatases in tibial epiphyses and weights as well as length and width in tibias and femurs of the embryos were determined. Tartrate-resistant acid and alkaline phosphatases ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Genotype and embryonic age interaction was not statistically significant for those bone parameters. Alfonso- Torres et al (2009) showed that there weren't found any significant interaction between incubation day and breeder age on weight and length of femur. They also reported that weight and width of bones in broiler embryos were affected by breeder age.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Genotype and embryonic age interaction was not statistically significant for those bone parameters. Alfonso- Torres et al (2009) showed that there weren't found any significant interaction between incubation day and breeder age on weight and length of femur. They also reported that weight and width of bones in broiler embryos were affected by breeder age.…”
Section: Discussionmentioning
confidence: 95%
“…The bones were weighed. Femur length was measured from the Trochanter major to Condylus lateralis and the width at the medial diaphysis (Alfanso- Torres et al, 2009). And they were stored at -20 ºC for further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…While our results deviate from those of the aforementioned ex ovo and ex vivo measurements, there were also discrepancies among those studies. For example, for d15 we measured a mean femur length of 8.574 mm, Alfonso-Torres et al [28] reported a length of 14.51 mm (by polynomial regression), and Hammond et. al reported a length of 11.25 mm (Figure 4(b) in [31]).…”
Section: Discussionmentioning
confidence: 99%
“…al reported a length of 11.25 mm (Figure 4(b) in [31]). In addition to human bias, these apparent differences may arise from variations in breeder age [28] and incubation temperature [31] as well as bone shrinkage resulting from fixation or preparation [33]. Our methodology imposes additional constraints that should be considered when comparing our measured lengths to those of classical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The weights of eggs and, accordingly, the weights of the chicks obtained increase with an increase in the breeder age (Şahan et al, 2014;İpek and Sözcü, 2015). Higher mortality (Wyatt et al, 1985) and lower yolk nutrients (Şahan et al, 2014) are observed in the eggs obtained from young breeders, whereas the bone width is higher in the embryos obtained from old hens (Alfonso- Torres et al, 2009). Shanawany (1987) and Peebles et al (1999a) put forward that the increase in the hatching weights of the chicks depending on the breeder age significantly increased the weights on the following weeks.…”
Section: Introductionmentioning
confidence: 99%